Human Capital and Wages in Exporting Firms - Jakob Roland Munch; Jan Rose Skaksen (Copenhagen Business School (CBS), Department of Economics, 2009)
This paper studies the link between a firms education level, export performance and wages of its workers. We argue that firms may escape intence competition in international markets by using high skilled workers to differentiate their products. This story is consistent with our empirical results. Osing a very rich matched worker-firm longitudinal dataset we find that firms with high export intensities pay higher wages. However, an interaction term between export intensity and skill intensity has a positive impact on wages and it absorbs the direct effect of the export intensity. That is, we find an export wage premium, but it accrues to workers in firms with high skill intensities.
hdl:10398/7623
Keywords: J30; F10; I20; 330; Exports; Wages; Human Capital; Rent Sharing; Matched Worker-Firm Data